2016
DOI: 10.1530/erc-16-0266
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of IGF2 regulatory regions to diagnose adrenocortical carcinomas

Abstract: Adrenocortical carcinoma (ACC) is a rare malignancy with a poor prognosis. Discrimination of ACCs from adrenocortical adenomas (ACAs) is challenging on both imaging and histopathological grounds. High IGF2 expression is associated with malignancy, but shows large variability. In this study, we investigate whether specific methylation patterns of IGF2 regulatory regions could serve as a valuable biomarker in distinguishing ACCs from ACAs. Pyrosequencing was used to analyse methylation percentages in DMR0, DMR2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 43 publications
1
29
2
Order By: Relevance
“…We included 17 publications (37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53) that contributed data to either the diagnosis of ACC in the context of adrenal vs non-adrenal distinction (4 studies) or in the context of benign vs malignant adrenocortical tumor distinction (15 studies) (two of them contributing to both subquestions (40,45)). Details of studies are shown in Appendix 1 (in all samples, diagnosis based on histological examination).…”
Section: Clinical Question 1: Pathologymentioning
confidence: 99%
“…We included 17 publications (37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53) that contributed data to either the diagnosis of ACC in the context of adrenal vs non-adrenal distinction (4 studies) or in the context of benign vs malignant adrenocortical tumor distinction (15 studies) (two of them contributing to both subquestions (40,45)). Details of studies are shown in Appendix 1 (in all samples, diagnosis based on histological examination).…”
Section: Clinical Question 1: Pathologymentioning
confidence: 99%
“…MDR1 mRNA expression was measured in cell lines and adrenocortical tissues. RNA isolation, cDNA synthesis and RT-PCR were performed as previously described, but using other primers (Supplementary Table 1, see section on supplementary data given at the end of this article; Sigma-Aldrich) (Creemers et al 2016b). Three housekeeping genes were used to normalize mRNA levels using the Vandesompele method: hypoxanthineguanine phosphoribosyl transferase 1 (HPRT1; Sigma-Aldrich), Beta-actin (B-actin; Thermo Fisher Scientific) and glucuronidase beta (GUSB; Thermo Fisher Scientific) (Vandesompele et al 2002).…”
Section: Real-time Quantitative Pcrmentioning
confidence: 99%
“…In mice, it has been shown that 5-azacytidine, which inhibits DNA methylation, causes hypomethylation of the ICR in the IGF2 gene (Figure 3). Since the maternal ICR in IGF2 gene is not methylated and as a consequence of 5-azacytidine treatment, ICR on the paternal IGF2 becomes hypomethylated and IGF2 expression from the paternal gene would be strongly inhibited [149]. In line with this, 5azacytidine treatment inhibited rhabdomyosarcoma cell growth through repression of IGF2 expression and re-expression of H19 in vitro [150].…”
Section: Igf2 Targeting In Cancer and Therapy Resistancementioning
confidence: 82%